PENGARUH PENGGUNAAN MEDIA SOSIAL TERDAHAP PROSES BELAJAR BAHASA INGGRIS SECARA DARING PADA MASA PANDEMI COVID-19 DI SMKN 9 KOTA TANGERANG - Sari, Desja Air; Isfahani, Rizki; Pratiwi, Ayu (Nusantara Hasana Berdikari, 2022)
The existence of this pandemic has an impact on the world of education, so teaching and learning activities at SMKN 9 Kota Tangerang are conducted online using Google Classroom and WhatsApp social media in order to stay connected with teachers in school. This research aims to find out the influence of social media use in the process of learning English online during the Covid-19 pandemic at SMKN 9 Kota Tangerang. This research uses a type of quantitative research, using descriptive methods of correlation. The study sample was determined using cluster random sampling, namely students of class XI SMKN 9 Kota Tangerang. Based on the results of the study, namely the use of social media obtained by students of SMKN 9 Kota Tangerang with high social media use as many as 60 students (80%), while the use of social media is low as many as 15 students (20%). While based on the results of research the online English learning process was obtained by students of SMKN 9 Kota Tangerang with the process of learning English online both as many as 48 students (64%), and the process of learning English less good as many as 27 students (36%). There is an influence on the use of social media with the process of learning English online with a value of P value 0.030.